Free moment application by athletes with and without amputations in linear and curved sprinting - Willwacher, S.; Funken, J.; Heinrich, K.; Alt, T.; Müller, R.; Potthast, W. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of the present study was to describe free moment (FM) application to the ground in high speed linear and curved running in athletes with unilateral amputations and non-amputee athletes. The results indicate that peak FM amplitudes are about three times higher in sprinting compared to running at distance running speeds. Curved running decreases internal rotation FM amplitudes of the right (outside) leg in nonamputee runners. The use of running specific prostheses (RSPs) is related to lower FM application in sprinters with unilateral amputations. This might be related to inertial asymmetries between legs or to constraints imposed at the RSP attachment interface. Monitoring FM patterns in sprint diagnostics might help athletes and coaches in the improvement of running and sprinting performance and overuse injury prevention.